If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 4(2x + -15) = -50 Reorder the terms: -6x + 4(-15 + 2x) = -50 -6x + (-15 * 4 + 2x * 4) = -50 -6x + (-60 + 8x) = -50 Reorder the terms: -60 + -6x + 8x = -50 Combine like terms: -6x + 8x = 2x -60 + 2x = -50 Solving -60 + 2x = -50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '60' to each side of the equation. -60 + 60 + 2x = -50 + 60 Combine like terms: -60 + 60 = 0 0 + 2x = -50 + 60 2x = -50 + 60 Combine like terms: -50 + 60 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| (k-1)=3x^2+3x+2 | | .25(x+.4)=.1x-1.6 | | x^2+9=x+17 | | -24-3y=-6(x+2) | | 0.12x+5-0.2x=0.37x-0.4 | | 7(2x-3)+3=6(2x-3)(2x-3) | | 6(x-6)=2x+2(x-8) | | 6s-11=-2+5 | | 6(-b+6)=30-6 | | 82+13x-68=8x+49 | | 22+4b=6(1+b) | | 3x+40=7x | | 2x+65=7x+5 | | 5-7n=-8+6n | | 1-e^16-x^2=0 | | 25x=1200+9x | | 2x+7(-4x-18)=186 | | 30+.10=200 | | 3x-(15-12x)=-3(5-5x) | | 24.8+(-8.7)-13= | | 4=1/4x | | m^10+7m^5+12=0 | | T(x)=-0.85x+9.6 | | 15(3-6)=56.25 | | (2+2)-(4*4)+(8-6)= | | 6x+9=7x+1 | | 22-5(6x-1)=63 | | 2(12-6x)=-3(9+4x) | | 8b-6b=18 | | 34+.5x=26 | | -2(5-n)=-7+5n | | 4(3x-5)=2x+90 |